Baranya megye és Tuzla kanton társadalmi-gazdasági változásainak összehasonlító elemzése - M. Császár, Zsuzsanna; Kolutácz, Andrea (Közép-Európai Közlemények, 2009)
This assay is about a comparison of two smaller regions, which are disadvantageous districts for the home countries. The base of the choose was the parallel past and profile. Discovering the interior problems of Baranya and Tuzla Counties can reserve practicable results for the members of the economy, politics and higher education. Tighter collaboration may effect the abatement of the peripherical situation of the area. It could also help evolving the euroregional mentality and it could extend the connector position between the EU and the Balcan territory by increasing the fascination. Our aim is to discover the tendencies of development, to assign the additional functions of the societal-economical-educational and cultural co-operation.